2023
DOI: 10.2186/jpr.jpr_d_21_00275
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of conventional and underprepared drilling preparation of the implant site based on bone density: A systematic review and meta-regression

Abstract: Currently, one of the most important challenges in dental implant surgery is the optimization of techniques to obtain a high grade of stability. This is a key factor for survival and long-term predictability, especially in immediate loading procedures [1]. Implant stability can be classified as primary and secondary, which represent the mechanical retention of the bone at the time of implant insertion and the formation of biologically stable bone around the fixture, respectively [2,3].A commonly used surgical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…A recent review has shown that there is a relationship between implant macro-geometry and the size of the osteotomy that can influence the osseointegration process [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review has shown that there is a relationship between implant macro-geometry and the size of the osteotomy that can influence the osseointegration process [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Toia et al [ 18 ] observed that marginal bone level (MBL) was influenced by bone quality, implant diameter, insertion torque value (ITV), and the interaction between bone quality and ITV. It was estimated that MBL was greater with increased bone density and ITV [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the different radiological possibilities that technology offers us, most authors have traditionally used it to analyze the bone density of the bone area that concerns us in surgery [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Underpreparation techniques could cause overheating or excessive compression of the cortical bone with the formation of microfractures [22]. The aforementioned authors recommend carefully selecting the drilling sequence based on bone density to achieve optimal primary stability and preserve crestal bone morphology [21]. In this way, it is important that the clinician knows how the surgical technique influences not only the PS but also all those factors that intervene in the success of implant therapy [17,18,23].…”
Section: Introductionmentioning
confidence: 99%